Implementasi Pembelajaran Sinkronus pada Mata Kuliah Fisika 1 Menggunakan Discord Dipadukan dengan Google Jamboard dan Powerpoint - Samuel Gideon; Abdul Azis Rahmansyah (Physics Education Research Journal, 2021)
COVID-19 virus have affected educational activities to be carried out through e-learning. Discord and Google Jamboard offer advantages in delivering synchronous e-learning. The purpose of this research is to implement e-learning of Physics 1 course using Discord integrated with Google Jamboard and Powerpoint. In this research, we used qualitative-descriptive method which conducted in several steps, i.e: (1) Discord installation and Physics 1 Class preparation; (2) Virtual Tablet Server installation and its testing for mobile phone; (3) Learning materials preparation in Powerpoint; (4) Implementation of Physics 1 Class using Discord integrated with Google Jamboard and Powerpoint; (5) Evaluation of the results and (6) Surveying of student’s opinion about e-learning using using Discord integrated with Google Jamboard and Powerpoint. Discord can be used as an alternative e-learning tool because of its practical use as well as more powerful when integrated with Google Jamboard and Powerpoint, especially for mathematical-analytics subject such as Physics. This is supported by the results of a survey in which 34 out of 39 students said they wanted to use Discord and Google Jamboard for other mathematical-analytics subjects.